Unchecked corporate power: why the crimes of multinational corporations are routinized away and what we can do about it - Barak, Gregg (Crimes of the powerful, 2017)
Preface -- Routinizing the crimes of the powerful -- Introduction: on the state routinization of unchecked corporate power -- Capitalism, corporations, and criminality -- Why capitalist states "fail" to control the crimes of the powerful -- Violating the commons -- Financial crimes : violations of trusted securities -- Environmental crimes : violations of health and safety -- Colluding crimes of states and corporations : violations of the community -- Halting corporate harm -- Checking corporate power and state-routinized crime in an age of global capitalism -- Conclusion: democratic capitalism, state owned multinationals, and sustainable pragmatism